Characterization and Screening Active Phytochemical Compounds of 70% Ethanol Extract of Mahogany Seed (Swietenia mahagoni Jacq.) - I Putu Gede Adi Purwa Hita; Putu Eka Arimbawa; Ni Putu Aryati Suryaningsih (Universitas Islam Negeri Alauddin Makassar, 2021)
One of the herbal medicinal plants in Indonesia with antidiabetic activity is mahogany (Swietenia mahagoni Jacq.). Differences in plant parts used, extraction methods, and solvents during the extraction process will result in different characterization, quantity, and active phytochemical compounds in the extract. This study aimed to determine the content of active phytochemical compounds and extract characteristics of mahogany seed that fit the standards. Extracts were made using the maceration method with 70% ethanol solvent, then extract was characterized, and phytochemicals of active compounds were screened using reagents according to each group of compounds' test method. 50.16 g of 70% ethanol extract of mahogany seeds produced in this study had a solid form, characteristic odor, bitter taste, and brown color. The extract has the characteristics of water content, total ash content, acid insoluble ash content, water-soluble extracts content, and soluble ethanol extracts content according to the standard. Several classes of active compounds were identified qualitatively in the extract, which are flavonoids, phenolics, terpenoids, steroids, glycosides, and saponins. It appears that 70% ethanol extract of mahogany seed has a characterize extract that meets the standards and contains several active phytochemical compounds as potential antidiabetic agents.